The Southern Ocean's Role in Carbon Exchange During the Last Deglaciation - Burke, Andrea; Robinson, Laura F. (SCIENCE, 2012)
Changes in the upwelling and degassing of carbon from the Southern Ocean form one of the leading hypotheses for the cause of glacial-interglacial changes in atmospheric carbon dioxide. We present a 25,000-year-long Southern Ocean radiocarbon record reconstructed from deep-sea corals, which shows radiocarbon-depleted waters during the glacial period and through the early deglaciation. This depletion and associated deep stratification disappeared by similar to 14.6 ka (thousand years ago), consistent with the transfer of carbon from the deep ocean to the surface ocean and atmosphere via a Southern Ocean ventilation event. Given this evidence for carbon exchange in the Southern Ocean, we show that existing deep-ocean radiocarbon records from the glacial period are sufficiently depleted to explain the similar to 190 per mil drop in atmospheric radiocarbon between similar to 17 and 14.5 ka.